Pelacuran Di Panti Pijat (Studi Kasus Perilaku Sex Menyimpang Di Panti Pijat Kebugaran Jasmani D’top Jalan Mira Seruni Kecamatan Penakkukang Kota Makassar) - Ajisaputra, Muh (Jurnal Inovasi Global, 2025)
The purpose of the study is to reveal 1) The factors behind the change in the function of the D'Top Massage Parlor, Penakkukang District, Makassar City. 2) The role of the government in preventing irregularities in the D'Top Massage Parlor, Penakkukang District, Makassar City, 3) The social implications of the existence of the D'Top Massage Parlor, Penakkukang District, Makassar City. Types of qualitative research with a case study approach with the location of the research at the D'Top Massage Parlor, Penakkukang District, Makassar City. The determination of informants by Purposive Sampling was 8 people, 3 expert informants, 3 key informants of the year, namely the Village Head, youth leaders, and the tourism office, and 2 ordinary informants, namely visitors. A type of qualitative research, with a phenomenological study approach, data collection techniques through Observation, Interviews and Documentation. Data analysis uses qualitative descriptive, namely data reduction, data presentation and conclusion drawn, as well as the validity of internal validity data and external validity. The results of the study: 1) the factors behind the change in the function of the D'Top Massage Parlor, Penakkukang District, Makassar City, are (1) a. factors from within, namely economic conditions, low education, and divorce, c. factors from outside, namely exploitation of employees, and abuse of illegal drugs. (2) the role of the government in preventing deviant behavior in the D'Top massage parlor, Panakukkang district, Makassar city, is limited to supervising. (3) The social implications for the existence of the D'Top massage parlor, Penakkukang District, Makassar City, cause pros because it brings jobs for prostitutes and contras because it brings social diseases among the people of Panakukkang.